Robust optimal R&D investment under technical uncertainty in a regime-switching environment. (3rd June 2022) - Wang, Ming-hui; Huang, Nan-jing
ABSTRACT: In this paper, we extend the classic optimal research and development (R&D) investment model into the regime-switching environment. We formulate a robust model to obtain the maximal net value function of the R&D project under a family of real-world measures, which can also be regarded as a stochastic differential game. Then, the verification argument is provided. Though we do not find the closed-form solution, we give a numerical simulation to further study the qualities of the solution to our model.